Case report: Liver PEComa after kidney transplantation in recipient with tuberous sclerosis complex - Dymkowski, Marcin; Kalman, Paulina; Niecikowski, Piotr; Koperski, Łukasz; Kosieradzki, Maciej (Frontiers in Oncology, 2024)
Introduction Perivascular epithelioid cell tumors (PEComa) are rare tumors of mesenchymal origin that exhibit perivascular epithelioid cell phenotype. One of its most common localizations is uterus, whereas only a few studies reported PEComa localization as liver. There is a correlation between the presence of PEComa and tuberous sclerosis complex (TSC). TSC is a rare disease which leads to the development of mostly non-cancerous tumors in various organs. We would like to present a case of a kidney transplant recipient with a PEComa detected post-transplant in the liver. Case report A 27-year-old patient, 3 years after kidney transplantation (KTx) due to chronic renal failure in the course of autosomal dominant polycystic kidney disease and concomitant TSC, was admitted to the Clinic and Department of General and Transplant Surgery for abnormal findings in computed tomography (CT). A CT scan was conducted for oncological follow-up after a kidney transplant (KTx) because before the transplantation, a small cystic lesion measuring 7 mm in diameter was removed from the donor kidney and diagnosed as papillary renal cell carcinoma (PRCC). Two tumors in the liver were detected - one 27mm in diameter in segment VII/VIII and the other 8mm in diameter in segment II/III. Because of typical radiological signs hepatocellular carcinoma was suspected, but the serum level of alpha fetoprotein was within normal limits and liver function was preserved. The intraoperative biopsy and the radiofrequency ablation (RFA) of the larger tumor were performed three months later. In the histopathological examination benign PEComa (HMB45 +, Melan A +) was detected. Conclusion The oncological surveillance made it possible to detect liver lesion in early stage and in 3,5-year follow-up no sign of recurrence of PEComa was found. This case is the second to show RFA as treatment method of liver PEComa and first in kidney transplant recipient.